Language Operative Capacity in Small and Medium-sized Enterprises - Ankita Tibrewal; Ad de Jong; Geoff Parkes; Helene Tenzer; Melissa Bel-Lahsen (Management International Review, 2024)
Abstract Language-related IB research predominantly targets large MNCs, often overlooking the challenges that internationalizing SMEs face in effectively utilizing their limited language resources. To address this gap and assist SMEs in overcoming their unique language challenges, we develop a scale for language operative capacity (LOC), which measures a firm's capacity to deploy language resources most productively throughout its global operations. We validate this instrument with data from 417 SMEs and examine its impact on two critical internationalization metrics: export performance and international networking capability. Our study makes three key contributions to language-related IB research and capacity research. First, we provide a comprehensive and robust LOC instrument, incorporating distinctions between potential and realized capacity from the capacity literature. Second, we offer a deeper understanding of language as a multi-level phenomenon by highlighting the interaction between individual-level language skills and organizational-level capacities. Third, we extend the scarce language-related IB research on SMEs by offering a nuanced understanding of LOC as a strategic resource, by validating the LOC instrument in the context of internationalizing SMEs, and by demonstrating its explanatory power for essential internationalization metrics. Additionally, our research provides SMEs with an actionable tool to assess their linguistic capacities, develop their language resources and optimize the use of these language resources in international operations.
Keywords: 330; Language operative capacity; SMEs; Internationalization; Export performance; Networking capability; Scale development